PERAN HUMAN RESOURCES DEVELOPMENT (HRD) DALAM MENINGKATKAN COMPETITIVE ADVANTAGE KARYAWAN PADA BTN SYARIAH KCPS PAREPARE - Andi Asrul Hamka; Moh Yasin Soumena; Abdul Hamid (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2022)
The purpose of this study was to determine the role of Human Resources Development in increasing the Competitive Advantage of employees at BTN Syariah KCPS Parepare. The formulation of this problem is (1) What is the role of HRD for employees of BTN Syariah KCPS Parepare?, (2) what steps are taken by HRD in increasing the competitive advantage of employees of Bank BTN Syariah KCPS Parepare?. The research method used is descriptive qualitative research to explain the implementation of the dual banking system at Bank BTN Syariah KCPS Parepare. This research will be conducted at Bank BTN Syariah KCPS Parepare. Primary data sources are bank employees as financing analysts and secondary data sources are relevant research journals. Data collection techniques are the methods of observation, interviews and documentation. Data analysis using Miles and Huberman, namely reduction, data display and conclusion drawing/verification. The results of the study show (1) The role of HRD in Bank BTN Syariah KCPS Parepare employees is very important, because with the existence of HRD the bank can more easily manage its employees, because it can organize, assess, provide training, and develop employees. Without HRD, the organization or bank will not run because HRD is the liaison between employees and the company. (2) The steps taken by HRD in improving its employees at Bank BTN Syariah KCPS Parepare are starting from looking for and selecting employees who are considered outstanding, providing training to employees who excel, so that employees are better trained with new things, so that able to develop new ideas or new innovations that can increase employee competitiveness. Keywords: The role of HRD, HRD in increasing the Competitive Advantage of Employees